KEPOLIMAKNAAN - Asep Wawan Jatnika (Fakultas Seni Rupa dan Desain ITB, 2008)
An ambiguous sentence is a sentence which has more than one possible meaning. In Bahasa Indonesia, an ambiguous sentence can be avoided by (1) putting the hyphen (-) within the phrase that is being referred to, (2) placing the word